Separating between unobserved consumer types: Evidence from airlines - Escobari, Diego; Hernandez, Manuel A. (Western Economic Association International, 2019)
We propose an alternative approach to identify unobserved consumer types and assess whether firms price discriminate. Unlike other screening schemes that rely on quantity discounts or product differentiation, in our finite mixture structure individuals have unit demands and the product is homogeneous. We implement the model using an original U.S. airlines data set. The results support the existence of two demand types. The high‐type “business” traveler is less price sensitive, has a higher valuation, and pays a higher price than the low type “tourist.” The proportion of high types also increases as the departure date nears. (JEL C23, L93, R41)